The Antecedents of Calling: A Career Construction Perspective - Ulfa, Bella; Riasnugrahani, Missiliana; Riantoputra, Corina D. (UI Scholars Hub, 2021)
Research Aims: This study aims to examine the moderating role of leader autonomy support (LAS) in the indirect relationship between cognitive flexibility and calling through job crafting. Design/methodology/approach: Data were collected through an online survey from employees who have been working at a private company for a minimum of one year. Using a convenience sampling method, data were collected from a total of 140 respondents. Data were analysed in SPSS using a moderated mediation model. Research Findings: The results showed that LAS moderated the indirect effect of cognitive flexibility on calling through job crafting. Theoretical Contribution/Originality: This study illustrates the complex relationship between cognitive flexibility, job crafting, and LAS as the antecedents of calling by drawing on career construction theory (CCT), while simultaneously emphasising the importance of situational factors (i.e., LAS) in finding a calling, especially for employees. Managerial Implication in the South East Asian context: Companies are expected to put more effort into understanding the role of individual and situational factors in their employees' journey toward finding a calling. Specifically, leaders' support for employees' job crafting should be strengthened to facilitate employees in discerning their work as a calling. Research limitations & implications: This study has limitations regarding the data collection, as it only uses a cross-sectional design. Additionally, this study only examines the antecedents of calling through employees' perception.